Effect of a Structured Education Program on Nursing Students' Awareness and Attitudes Towards Violence Against Women: A Quasi-Experimental Study - Öztürk, Ayfer; Albayrak, İrem; Güler, Berşan; Morkoç, İlayda; Kaçan, Hüseyin; Öztürk, Ayfer (My University, 2024)
Objective: This study aims to evaluate how “Awareness Education on Violence Against Women” (AEVAW) affects the knowledge levels of nursing students regarding domestic VAW and their attitudes. Method: This study is in a pretest-posttest quasi-experimental research design with experimental and control groups and was carried out on the nursing students attending the health sciences faculty of a state university in Turkey. Of the 65 students who agreed to participate in the study, 33 were included in the education group and 32 were included in the control group. Study data were collected using a descriptive information form, Scale for Nurses and Midwives to Determine the Symptoms of Violence against Women (SNMDSVAW), ISKEBE Violence Against Women Attitude Scale (ISKEBE VAWAS), and Domestic Violence Against Women Knowledge Test (DVAWKT). In all measurements (pretest and posttest), three of these measurement tools were applied to both groups. Results: The posttest mean scores were higher for those trained, with significant increases in DVAWKT, SNMDSVAW, and ISKEBE VAWAS compared to pretest scores. AEVAW effectively enhanced nursing students' knowledge and awareness of VAW. Conclusion: Considering these results, it is recommended to include courses on VAW in the education curriculum of nursing students and to make these courses compulsory.
Keywords: Education; knowledge; attitude; Women; domestic violence; awareness